2022
DOI: 10.1155/2022/6444747
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of Hyperbaric Oxygen Combined with Astaxanthin Mediating Keap1/Nrf2/HO-1 Pathway to Improve Exercise Fatigue in Mice

Abstract: Objective. This work aimed to explore the application and optimization of the electrophysiological monitoring system to real-time monitor the exercise-induced fatigue (EIF) animals and investigate the intervention mechanism of hyperbaric oxygen (HBO) combined with natural astaxanthin (NAX) on EIF. Methods. First, a system was constructed for acquisition, processing, and feature extraction of electrocardiograph (ECG) signal and surface electromyography (EMG) signal for EIF monitoring. The mice were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Elevated ROS will not only lead to an imbalance of the redox system in the body, but may also trigger the lipid peroxidation of the mitochondrial membrane and disrupt mitochondrial functions, affecting energy supply and ultimately leading to fatigue [ 44 , 45 ]. Additionally, excessive free radicals produced during exercise can lead to multiple cell/organelle damage and tissue/organ pathophysiological changes, thereby affecting exercise capacity [ 46 , 47 ].…”
Section: Pathogenesis Of Exercise-induced Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Elevated ROS will not only lead to an imbalance of the redox system in the body, but may also trigger the lipid peroxidation of the mitochondrial membrane and disrupt mitochondrial functions, affecting energy supply and ultimately leading to fatigue [ 44 , 45 ]. Additionally, excessive free radicals produced during exercise can lead to multiple cell/organelle damage and tissue/organ pathophysiological changes, thereby affecting exercise capacity [ 46 , 47 ].…”
Section: Pathogenesis Of Exercise-induced Fatiguementioning
confidence: 99%
“…Furthermore, as a typical cellular antioxidant regulator at the transcriptional level, nuclear factor erythroid-derived 2-like 2 (Nrf2) can control the basic and induced expression of a series of antioxidant response element-dependent genes [ 69 , 97 ]. Studies have proven that the activation of the Kelch-like ECH-associated protein 1 (Keap1)/Nrf2/heme oxygenase-1 (HO-1) pathway is the dominant mechanism of cellular defense systems against oxidative stress, and it also participates in enhancing the exercise-induced fatigue state [ 47 , 94 ]. Usually, Nrf2 is present in the cytoplasm and binds to the inhibitory protein Keap1, but the activated Nrf2 can promote its separation from Keap1, subsequently binding to the antioxidant response element in the nucleus to control the transcriptions of downstream genes (SOD, CAT, and HO-1) and exacerbate its anti-oxidation ability [ 3 , 97 ].…”
Section: Polysaccharides Ameliorate Fatiguementioning
confidence: 99%
“…Astaxanthin ( Zhang and Gao, 2022 ), sulforaphane ( Ruhee and Suzuki, 2020 ), gastrodin ( Zhang et al, 2023 ), and embryo chicken egg extract ( Zhang et al, 2021 ) enhance antioxidant stress and improve exercise tolerance in mice by interfering with the AMPK and Nrf2 signaling pathways. Extracts of A. japonica were found to contain dithranolone, which is the most biologically active substance in A. japonica .…”
Section: Signaling Pathways Affected By Natural Active Ingredients Ag...mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%